Cupboard Love : The Lady of the Barge and Others, Part 5. - Jacobs, W. W. (William Wymark), 1863-1943; Greiffenhagen, Maurice, 1862-1931; Richards, Amy, active 1896-1918 (Salt Lake City, UT : Project Gutenberg, 2004)
"Cupboard Love" by W. W. Jacobs is a humorous short story set in the early 20th century. This narrative revolves around a theft of a brooch from the home of Mrs. Negget, whose retired policeman uncle, Mr. Martin Bodfish, takes on the role of detective. The story explores themes of suspicion, family dynamics, and the quirks of human behavior as the characters navigate the complexities of their relationships and the unfolding mystery surrounding the missing item. In this tale, Mrs. Negget has discovered her gold brooch missing, prompting a lively discussion among family members as they try to deduce how it could have disappeared. Tensions rise as uncle Bodfish investigates, questioning the household staff and exploring various angles, while farmer Mr. Negget$1 (Bs efforts to divert suspicion humorously complicate matters. As the story unfolds, it becomes clear that personal relationships and misunderstandings drive the narrative, culminating in a comical climax when Mr. Bodfish is caught in a compromising position while searching the widow's cottage, which leads to the unexpected resolution of the mystery. The overall tone is light-hearted, showcasing Jacobs' talent for blending humor with a touch of intrigue. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; River life -- Fiction